Archaeological discontinuity in Ultima Esperanza: A supra-regional overview - Borrero, Luis Alberto; Martin, Fabiana Maria (My University, 2018)
The regional archaeological discontinuity between ca. 11,761 +/- 272 Cal BP and the beginning of the Holocene at Ultima Esperanza, Chile will be discussed. The absence of humans as measured by the deposition of artifacts on dated deposits was originally detected at the site scale, especially at Cueva del Medio and Cueva Lago Sofia 1, but recent excavations at several other sites extend it to the full scale of the Cerro Benitez locality. It is suggested that this is not a case of abandonment of a colonized region, but instead a case of discontinuation in the logistical use of a particular environmental patch. Accordingly, the Early Holocene human presence in the Cerro Benitez locality is seen as the result of a new exploration by human foragers adapting to the increasingly forested environments of Ultima Esperanza. (C) 2017 Elsevier Ltd and INQUA. All rights reserved.
Keywords: patagonia; archaeology; pleistocene; holocene; discontinuity; exploration